Light-driven removal of rhodamine B over SrTiO3 modified Bi2WO6 composites. Issue 86 (5th September 2016) - Zhang, Li; Tian, Wei; Chen, Yong; Chen, Jing; Teng, Hongcheng; Zhou, Jiancheng; Shi, Jinwen; Sun, Yueming
Abstract : Heterostructures are closely related to enhanced photocatalytic function of SrTiO3 /Bi2 WO6 hybrids. Abstract : SrTiO3 /Bi2 WO6 hybrids were hydrothermally prepared and structurally examined by means of various chemical and physical techniques. Formation of heterojunction is well confirmed via HRTEM, XPS and PL and contributes immensely to the enhanced catalytic function of a composite in an assay of Rhodamine B (Rh B) photodegradation due to accelerated migration and separation of charge carriers at it. Among as-prepared samples, Bi2 WO6 loaded with 8 wt% SrTiO3 proves most photocatalytically active in light of a top degradation rate ( D ) of ca. 98.4% and a peak apparent kinetic rate ( k ) of 0.0463 min −1 . Besides, h + and ·OH turn out to be the major reactive species for Rh B degradation. Finally, based on theoretical and experimental results, a possible reaction mechanism was proposed.